The Influence of Halal Perception, Trust, and Social Influence on Gen Z Purchasing Decisions in Social Commerce - Bagus Pribadi; Muhammad Nashiruddin Darajat (Economos : Jurnal Ekonomi dan Bisnis, 2025)
The rapid growth of social commerce in Indonesia has transformed consumer behavior, particularly Generation Z, who increasingly consider halal aspects, trust, and social influence in their purchasing decisions. This study aims to analyze the influence of halal perception, trust, and social influence on Generation Z (Gen Z) purchasing decisions in the context of social commerce. Gen Z, as digital natives, drives the growth of platforms such as TikTok Shop and Instagram Shopping, where their consumption decisions are heavily influenced by social dynamics and personal values. A quantitative method was used by distributing an online questionnaire to 150 Gen Z respondents in Indonesia who have experience shopping on social commerce. Data were analyzed using multiple linear regression analysis techniques. The results revealed that halal perception, trust (in sellers and platforms), and social influence (such as influencer recommendations and reviews) simultaneously and partially have a positive and significant effect on purchasing decisions. These findings emphasize that amidst digital trends, trust and halal assurance factors remain critical considerations, while social influence plays a key role. The implications of this study provide guidance for business actors to develop marketing strategies in social commerce that integrate product halal transparency, build a trusted reputation, and effectively leverage the power of the community.